2018
DOI: 10.1186/s13045-018-0649-6
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of secondary poor graft function post allogeneic hematopoietic stem cell transplantation with eltrombopag

Abstract: Poor graft function (PGF) is a life-threatening complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Current treatment strategies include the use of growth factors, CD34+-selected stem cell boost, mesenchymal stem cell transfusion, and second allo-HSCT, but these treatments are not effective in all patients. Eltrombopag, an oral thrombopoietin receptor agonist, which showed promising results in severe aplasia anemia, may be an alternative choice for PGF patients. Therefore, we tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…Due to its effects on platelet counts and hematopoietic stem cells [2], however, the anti-HCMV effects of eltrombopag are primarily of relevance for anemia patients at risk of HCMV disease, for whom eltrombopag is indicated. Eltrombopag has been suggested for the treatment of cytopenias after hematopoietic stem cell transplantations and case reports support its safety and efficacy [4][5][6][7][8][9]. Since HCMV reactivation and HCMV-associated diseases are leading reasons for the failure of hematopoietic stem cell transplantations [10][11][12], antiviral effects exerted by eltrombopag may also contribute to improved therapy outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its effects on platelet counts and hematopoietic stem cells [2], however, the anti-HCMV effects of eltrombopag are primarily of relevance for anemia patients at risk of HCMV disease, for whom eltrombopag is indicated. Eltrombopag has been suggested for the treatment of cytopenias after hematopoietic stem cell transplantations and case reports support its safety and efficacy [4][5][6][7][8][9]. Since HCMV reactivation and HCMV-associated diseases are leading reasons for the failure of hematopoietic stem cell transplantations [10][11][12], antiviral effects exerted by eltrombopag may also contribute to improved therapy outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Eltrombopag is a thrombopoietin receptor (also known as c-Mpl or MPL) agonist that is used for the treatment of thrombocytopenia, including hepatitis C virus-associated thrombocytopenia [1][2][3]. Its use has also been suggested for the treatment of cytopenias after hematopoietic stem cell transplantations and case reports support its safety and efficacy [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, given the data on the efficacy of TPO agonists in various bone marrow failure syndromes and other diseases associated with cytopenia, and the safety of their use in malignant diseases, as well as its ability to overcome the immune mechanisms of suppressing hematopoiesis, TPO-RA seem to be good candidates for management of PGF. Recently, the several groups published the experience of TPO-RA administration in post-transplant setting [28,29,30]. Nevertheless, the precise analysis of efficiency of this therapy is complicated, due to small number of patients and different inclusion criteria in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies defined response by freedom from platelet transfusion, 34 others by normalization of platelet count, [35][36][37] and others by a target platelet threshold of ≥50 000/µL. [38][39][40][41][42][43][44][45] The best approximation of the combined overall response rate for both agents was 71% (Figure 1).…”
Section: Clinical Studies Of Tro Mimetics After Allogeneic Hctmentioning
confidence: 99%
“…Twelve reports of 119 patients with prolonged thrombocytopenia post HCT were included in this review as shown in Table 3. [34][35][36][37][41][42][43][44][45][58][59][60] An additional 67 patients were treated with eltrombopag in articles that reported outcomes combined with romiplostim as shown in Table 4. [55][56][57] Two reports included pediatric patients.…”
Section: Eltrombopag For Delayed Thrombocytopenia Following Hctmentioning
confidence: 99%